GUIDELINES FOR COST-EFFECTIVE GEOVISUALIZATION IN DIGITAL FORENSICS - MARIANNA ZICHAR (Acta Geographica Debrecina. Landscape & Environment Series)
Every field of our life is influenced by the appearance of new technologies. This means that new challenges keep being met and finding solutions, developing methods to deal with them belong to our tasks. Law enforcement has to be always ready to adopt the achievements of any disciplines. Experts and professionals in any field should be aware of applicability of the knowledge they have that is why it is important to highlight as much fields where our knowledge can be used as we can. Digital forensics differs from traditional forensics in many aspects that is why a general GIS professional can be involved into an investigation easily. This paper aims to provide methods to geovisualize information containing or referring to location data. Cost effective solutions are preferred throughout the paper